Analysis of leadership and team management skills of middle-level healthcare managers of Valsad district, Gujarat - Neha A Patel; Sunil N Nayak; Bhaveshbhai R Bariya; Mehulkumar N Patel (Journal of Family Medicine and Primary Care, 2024)
Background: The healthcare managers need to develop the managerial skills and use it for better healthcare delivery. A manager requires leadership skill to empower employees and motivate them to work in an efficient manner to achieve organizational goal. Motivating employees/subordinates and developing positive attitude toward them is one of the crucial skills that the leader needs to develop. The way health team works as a unit affects the outcome and needs good leader. With this background, the current study tends to explore the managerial skills of middle-level managers. Objectives: 1. To assess the leadership and team management skills of middle-level managers and 2. To find out motivational factors used by managers. Materials and Methods: A cross-sectional study was conducted among district-level healthcare managers and medical officers. Data collection was performed via semistructured and scale-based questionnaire and analyzed using Microsoft office excel. Results: 60% of managers had participative leadership style. Team work skills were fair enough among the managers. 53% of medical officers were freshly appointed with experience of less than one year. The middle-level managers used appreciation of work (41.8%) as major motivator of the team. Conclusions: The middle-level healthcare managers have good leadership quality as well as teamwork skills. Appreciation of work is commonly used motivator.